Semiotic of Symbolic Mode in Interpreting Mythology in English Poetry - Mulyoso Mulyoso (TEFLIN Journal: A publication on the teaching and learning of English, 1999)
This paper is primary based on the assumption that we need theories of literature in order to interpret the literary texts and explain literature as a unique form of communication. The so-far traditional efforts of treating literary study as an intuitive analysis has contributed to the harsh criticism on the study of literature as merely Ã¢â¬Ëthe reading and understanding of literature. Literature teaching has given too much emphasis on the enjoying and understanding of a literary piece, that is to say that merely by understanding the meaning of the language of a text, its cultural references, one is said to be in a position to respond critically to that text Ã¢â¬â thus there is no need for interpretation beyond that. Therefore, this paper is an attempt to interpret a literary text (mythology in English poetry) beyond its literal level by the use of semiotics of symbolic mode approach which allows the intertextual and intratextual analysis.